Monolithic ultra‐low‐power 6 Gbit/s inductorless PRBS generator for silicon HBT‐based carrier‐injection electro‐absorption modulator. Issue 12 (1st June 2015) - Fu, E.; Koomson, V.J.
Abstract : A low‐power pseudo‐random bit sequence (PRBS) generator for testing a high‐speed optical transmitter module has been realised in a 130 nm bipolar CMOS process. The transmitter consists of a monolithic driver circuit architecture and a heterojunction bipolar transistor (HBT)‐based carrier‐injection electro‐absorption modulator. A 10 Gbit/s current mode logic latch with only 0.6 mW power consumption is designed by scaling down the current density without degrading the overall transmitter speed performance. The 2 7 −1 PRBS generator circuit consumes only 42.75 mW at 6 Gbit/s operating speeds with a 1.5 V dc power supply. The core circuit power consumption is 9 mW.